PROBLEMS OF MECHANICAL ENGINEERING DEVELOPMENT IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Mechanical engineering in synthesis with the IT sector forms a sector of the world economy with the highest potential for the creation and implementation of commodity, technical and technological innovations, which in modern conditions are crucial to ensure the prospects for socio-economic development and provide its high level in any country. However, Ukrainian mechanical engineering lags behind most EU countries in terms of its contribution to the economy, although it has sufficient production and resource potential, as well as human capital to function effectively. Accordingly, the aim of the article is to identify problematic issues of mechanical engineering productions’ development in Ukraine and substantiate ways to handle them. It has been proved that destructive transformations in mechanical engineering industry were the main reasons for the negative dynamics of this segment of Ukrainian industry and were caused by: a) disregard for national economic interests, especially in the agreements on accession to the WTO and FTA with the EU; b) ineffective state policy on the creation of favorable conditions for attracting capital investment in mechanical engineering production. The increase in imports of mechanical engineering products to Ukraine while reducing gross value added, output and exports of domestic enterprises became the negative consequences of the mentioned above processes. As a result, it has led to increased import dependence of the national economy in all segments of consumption (intermediate, final, gross fixed capital formation) of engineering products. The negative balance of foreign trade in these products became an indicator of such increased import dependence. Risks for socio-economic development related to the intensification of foreign mechanical engineering companies’ activities in Ukraine, especially those working on tolling schemes, have been substantiated. Challenges and threats to the domestic mechanical engineering industry, which may increase in conditions of global instability, in particular under the influence of Russian aggression, have been outlined. The priority directions of the state industrial policy for stimulating the development of mechanical engineering productions in Ukraine have been determined. They include: formation of a reliable system of scientific-technical and industrial cooperation; encouraging business development and domestic investment – investment in equipment upgrades and modernization should be the priority areas of the latter; strengthening the motivation of foreign companies to relocate production to the territory of Ukraine and attract investment from international companies; development of an institutional system for export promotion; large-scale import substitution, etc. Prospects for further research in this direction are seen in the scientific and analytical justification of the role of mechanical engineering (as a strategic segment of industry) in ensuring balanced interaction of all sectors of the national economy.
Keywords: mechanical engineering, products, production, export, import dependence, intermediate consumption, national economic interests.